(untitled) (Comprehensive Journal of Science, 2026)
The rapid evolution of Internet of Things (IoT) technologies and cloud computing has opened the door for the development of various possibilities for the management and exchange of data among interconnected devices. Cloud computing offers a flexible infrastructure for the management and processing of vast amounts of data from the massive data generated by IoT technologies. On the other hand, IoT technologies have the capability to continuously collect real-time data from different environments and transmit it through the use of various communication networks. The integration of these two technologies offers the possibility for the development of innovative smart services and applications, such as smart homes, intelligent transportation systems, and industrial predictive maintenance. However, the integration of IoT technologies with cloud environments presents various technical challenges, including security and privacy, network, and data management. The paper presents the major aspects of the integration of these two technologies and the various possibilities for addressing the challenges while leveraging the benefits of the integration of these technologies.